2009
DOI: 10.1210/en.2008-1335
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 18 and 124a Down-Regulate the Glucocorticoid Receptor: Implications for Glucocorticoid Responsiveness in the Brain

Abstract: Glucocorticoids (GCs) exert profound effects on a variety of physiological processes, including adaptation to stress, metabolism, immunity, and neuronal development. Cellular responsiveness to GCs depends on numerous factors, including the amount of the glucocorticoid receptor (GR) protein. We tested the hypothesis that micro-RNAs (miRs), a recently discovered group of noncoding RNAs involved in mRNA translation, might control GR activity by reducing GR protein levels in neuronal tissues. We tested a panel of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
143
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(156 citation statements)
references
References 47 publications
8
143
1
2
Order By: Relevance
“…Another level of fine-tuning GR levels can be provided by miRs, by directing mRNA destabilization and translational repression (91). Recently, it was reported that miR18 and miR124a reduce GR expression, which leads to impairment of the transcriptional response of GR (92). Therefore, TNF␣ might induce the expression of GR down-regulating miRs.…”
Section: Discussionmentioning
confidence: 99%
“…Another level of fine-tuning GR levels can be provided by miRs, by directing mRNA destabilization and translational repression (91). Recently, it was reported that miR18 and miR124a reduce GR expression, which leads to impairment of the transcriptional response of GR (92). Therefore, TNF␣ might induce the expression of GR down-regulating miRs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to 1 miR-18, which was expressed in numerous tissues, miR-124a expression was restricted to 2 certain brain regions and changed during the stress neonatal hyporesponsive period [85]. 3…”
mentioning
confidence: 98%
“…We found that forced swimming results in increased DNA methylation of the Nr3c1 gene associated with an enhanced binding of DNMT3A, which may explain the reduction in gene expression after stress. Furthermore, as it has previously been shown that the microRNA mir-124a can reduce GR mRNA expression in vitro [60], we investigated the expression of this microRNA under baseline conditions and after FS stress in vivo. Forced swimming indeed evoked a significantly increased expression of mir124a in the DG, which was negatively correlated with the expression of GR mRNA expression.…”
Section: Histone and Dna Methylationmentioning
confidence: 99%